(3GdfhGOQs - (3CHj Ydj ESeGYjd Hf GdbGSe GdbGdj GdHZOGOj,J (B356 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj Ld Yf THg GdNdjbI, hJYGdi Yf GdCaYGd GdbHjMI, hJfRg Yf GdLhQ, hJcHQ Yf GdXde s
(3BNQgG (B:s
(3CfTOfj CHhHcQ Hf OQjO QMeg Gddg GSJJH JgjC hGdJCe hCfLGO(B: (3LeY fLO s
(3GdfSNI HgG HYV GdVHWs
(3GfXQ GdbSe GdKGfj GdGQbGe (B993 - 997 (3COHs
(3HgG fXGe GdJYbjHIs
(3UaMJgG GdChdi eRhbI s
(3aj GdCNHGQ hGdCTYGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs